Psychosocial risks: Health and wellbeing of workers in petrochemical industry of Malaysia - Javaid, M.U. (Institute of Electrical and Electronics Engineers Inc., 2015)
Globally, there is an ongoing effort for all the working population to provide them with safe and healthy workplace environment. World Health Organization has disseminated the goal of promoting health in the work place by controlling the psychosocial risks at work in their global plan of action 2008-2017. Yet, WHO finds that the limited focus on psychosocial and work related stress creating deteriorating effect on safety, health and risks associated with the workplace environment within and amongst countries. Copenhagen psychosocial work environment factors will be used in this proposed study to hypothesize the relationship between psychosocial risks and its effect on health and wellbeing with the help of job demands-resources theory. Mixed methods approach i.e. qualitative and quantitative methods of data collection and/or analysis will be used for this study to attain and achieve a range of outcomes. To the best of researcher's knowledge this is the first proposed study where biomarker (blood pressure) is going to be used to measure the health and well-being in public health perspective in relation to psychosocial workplace factors in the petrochemical industry of Malaysia. Â© 2015 IEEE.